Seismic behavior of RC building structures designed according to current codes. (August 2016) - Mosleh, A.; Rodrigues, H.; Varum, H.; Costa, A.; Arêde, A.
Abstract: Earthquakes which recently occurred in highly populated regions show that existing buildings constructed without appropriate seismic resisting characteristics may constitute as an important source of risk and may cause economical loses and casualties. It is recognized the progress of the knowledge in earthquake engineering in the last decades. In this paper, two 6 irregular storey buildings were studied consisting of frame structures, representative of the common practice in Portugal, i.e. designed without considering earthquake actions. Push-over and non-linear time history analyses were done, with non-linear 3-D models in longitudinal and transverse directions. The building responses were analyzed in two different levels: global and local. For the global response analyses: max displacement, inter-storey drift (IS drift), floor rotation for each storey and base shear were compared. For local response four columns were chosen and the variation of axial load in terms of base shear and drift as well as the biaxial demand was considered. The result shows that most variation of axial load happens in corner, facade-X, facade-Y and centre column respectively. It is noteworthy that by increasing the initial axial load the biaxial demand decreases. The seismic vulnerability was analyzed for earthquake of different return periods, and the seismic demands were compared with limit proposed in international codes and conclusion are drafted in terms of safety. The vulnerability assessment based on seismic codes clearly shows that the building 2 presented a better performance with low inter-storey drifts. The main goal of this study is considering the application and methodology for the seismic assessment of existent real buildings. In fact this is an important topic, to understand the seismic vulnerability of certain particularities in existing buildings to assure that the common observation can be applied for a prototype building, especially irregular ones. Also one of the major observations in this study is the comprehension of the effect and importance of biaxial loading in columns and the influence of the axial load variation, relating the position of the columns in plan and in height.